The Role of Entrepreneurial Competencies in Strengthening Business Resilience: A Case Study of Young Entrepreneurs in Central Java - Ramadhan, Muhammad Syah Fibrika; Fauzi, Pahrul; Hidayah, Asmi Ayuning (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
This study highlights the importance of entrepreneurial competencies for young entrepreneurs, particularly in facing the increasingly competitive and uncertain business environment. Utilizing five dimensions of entrepreneurial competencies—opportunity competency, relationship competency, strategic competency, conceptual competency, and organizing competency—this research aims to analyze the level of entrepreneurial competencies among young entrepreneurs mentored by the Youth, Sports, and Tourism Department (Disporapar) of Central Java. Additionally, the study explores the influence of gender and business sectors on the level of entrepreneurial competencies. The research analysis employs one-way ANOVA with 184 young entrepreneur respondents. The results show that relationship competency is the most dominant aspect of entrepreneurial competency, while gender and business sectors significantly affect several aspects of entrepreneurial competencies, particularly relationship, strategic, and organizing competencies.